Analisis Keterampilan Siswa dalam Menyajikan Data Menggunakan Pendekatan PMR Berbantuan Papan Diagram Batang di SD Gondang Manis 01 - Fajriyah, Tsaltsa Nurul; Zahra, Nadhifa Safiratuz; Zuliana, Eka (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The use of bar chart boards is an effort to implement data presentation learning with the use of media as an aid. The main objective of this study is to implement bar chart board media based on Realistic Mathematics Education (PMR) to improve students' understanding in presenting data, as well as to encourage students' skills in presenting data accurately, completely, and clearly. The research method used is qualitative narrative with data collection techniques in the form of observation, interviews, and documentation. The subjects of this study involved students and teachers at SD Gondang Manis 01. Data were collected through various techniques, namely observation by observing student interactions with learning media and the role of teachers in classroom management, in addition we also use interview techniques with students and teachers to dig deeper into their experiences and perceptions. Thus, it is expected to be known to what extent the use of bar chart board media can help students understand statistical concepts and improve data presentation skills